Humor dalam Anime Gekkan Shoujo Nozaki-Kun - Devia Rizka Athaariqaa (Japanese Research on Linguistics, Literature, and Culture, 2019)
The purpose of this study was to describe humor based on the theory of incongruity in the ã€ŒæœˆåˆŠå°‘å¥³é‡Žå´Žãã‚“ã€â€ Gekkan Shoujo Nozaki-kun â€œ anime and categorized based on Graeme Ritchie theory. The data of this study were Nozaki Umetarouâ€™s and Seo Yuzukiâ€™s utterances in the Gekkan Shoujo Nozaki-kun anime which assumed to contain incongruity in the characterâ€™s utterances thus creating humorous effect. The data were then gathered and analyzed based on the theory of incongruity by Immanuel Kant and categorized based on Graeme Ritchie theory. The research method used in this study was descriptive qualitative and under the study of pragmatics. In the Gekkan Shoujo Nozaki-kun anime, the researcher found 20 dialoguesÂ  by Seo Yuzuki and Nozaki Umetarou which contained incongruity. The results of this study are, humour can be happened because the speaker's speech does not match with the expectations by the speech partner, then causing the speech partner to be surprised. The shock was realized as something funny by the speech partner. The types of incongruity that occur were inappropriateness, contrast, and conflict.